Mozart, Luigi Bassi, and ‘Fin ch’han dal vino’ - Tessing Schneider, Magnus (Danish Yearbook of Musicology, 2010)
The article focuses on the performance of the aria ‘Fin ch’han dal vino’ from Mozart’s Don Giovanni (1787) by the original leading baritone, Luigi Bassi (1766–1825). While no fi rt-hand accounts of Bassi’s performance are extant, a number of hitherto unknown or disregarded second-hand accounts and anecdotes were committed to paper in the nineteenth century. Examining these in detail, the article argues that both Mozart and Bassi favoured a charming, light-hearted, dynamically varied, not too rapid and basically comical performance of the aria. Perhaps due to the influence of Friedrich Rochlitz’s adaptation of the opera (1801) as well as to E. T. A. Hoffmann’s literary interpretation (1812), however, it was quickly reinterpreted on romantic premises by scholars as well as performers. This interpretation forms the basis of the modern conventional performance of the number, which favours extreme speed and an expression verging on the demonic or violent. Finally, the article compares the descriptions of Bassi’s performance to Søren Kierkegaard’s characterization of the aria (1842), arguing that the latter reflects a Danish performance tradition ultimately descended, through a series of influences, from Bassi.